Isolasi dan Identifikasi Jamur Mikroskopis Pada Ikan di Danau Perintis Provinsi Gorontalo - Mardin, Herinda; D. Uno, Wirnangsi; M. Hasan, Ani (Universitas Cokroaminoto Palopo, 2023)
Perintis Lake is a lake that is used by the community to fulfill their daily needs. Various types of fish that live in this lake are used as food for the community. Apart from that, Lake Perintis also has various organisms that live in it, including mushrooms. Fungi that live in waters are usually parasitic or saprophytic which if consumed can cause allergies or cause poisoning in humans. This study aims to isolate and identify the types of fungi present in fish in Lake Perintis. The method used in this study was the plate count method which included dilution, embedding into saburaud medium, and counting colonies. The results showed that there were three types of microscopic fungi in the fish in Lake Perintis, namely Saprolegnia sp, Aspergillus flavus, Rhizopus sp.